STUDI TENTANG BRAND PREFERENCE UNTUK MENINGKATKAN MINAT LOYALITAS PENGHARUM RUANGAN - Dafiq, Muhammad Arief Athfal; Widiyanto, Ibnu (Diponegoro Journal of Management, 2016)
The purpose of this study to give empirical evidence whether Brand Image and Product Quality influence on Brand Preference and Loyalty Intention of Consumer.            The sample of this study are 400 people in Kudus that use Glade Fragrances. Method of analysis data use quantitative analysis with multiple linear regression analysis.            The results of this study shows that the Brand Image and Product Quality give positive effect on Brand Preference with the regression coefficient  Y1 = 0.405 X1 + 0.329 X2. While Brand Image, Product Quality and Brand Preference give positive effect on Loyalty Intention of Consumer with regression coefficient Y2 =  0,658 X1 + 0,083 X2 + 0,206 Y1.